Immunocompatibility and Toxicity Studies of Poly‐L‐Lysine Nanocapsules in Sprague–Dawley Rats for Drug‐Delivery Applications. (19th May 2014) - Ayyappan, Janeesh Plakkal; Sami, Haider; Rajalekshmi, Dhanya Chandrasekharan; Sivakumar, Sri; Abraham, Annie
Abstract : Poly‐L‐Lysine (PLL) nanocapsules are the emerging drug‐delivery vehicle for the therapeutics of targeted diseases. The study was designed for the synthesis and characterization of PLL nanocapsules and to know its immunocompatibility and toxicity behavior for in vivo drug‐delivery applications. Alteration in hematologic parameters, immunomodulatory gene expression by RT‐PCR studies, toxicity markers status, immunoblotting of major inflammatory marker proteins, and histopathologic studies from major tissues of rat after intravenous administration of PLL nanocapsules after 30 days were assessed. In vivo toxicity markers activity, hematologic parameters alteration, and RT‐PCR analysis of important immunomodulatory genes such as monocyte chemotactic protein‐1(MCP 1), tumor necrosis factor‐alpha (TNF‐ α ), Intercellular adhesion molecule‐1 (ICAM‐1), and interleukin‐6 (IL‐6) showed least changes when compared with control. The immunoblotting of major inflammatory markers such as cyclooxygenase‐2 (COX‐2), lipo‐oxygenase‐15 (LOX‐15), and nitric oxide synthase (NOS) found have least expression showing the immunocompatibility of PLL nanocapsules. Histopathologic studies of important tissues showed almost normal architecture after treatment using different concentration of PLL nanocapsules after the experimental period. The results showed a promising outcome and further confirmed the immunocompatibility and non‐toxicity of PLL nanocapsules in vivo for drug‐delivery applications. Abstract : Poly‐L‐Lysine (PLL) nanocapsules were synthesized by template based approach and characterized by scanning electron microscopy and found to be 360 nm in size. In vivo toxicity markers activity, hematologic parameters alteration, RT‐PCR analysis of important genes, and immunoblotting showed least changes when compared with Groups I and II. The result of our study provides the information about the immunocompatibility and non‐toxicity of PLL nanocapsules for drug‐delivery applications in vivo .